Conscientiousness and academic stress among thesis-writing students - Nurtamami, Ismi; Wahidah, Fatin RN; Na'imah, Tri (ProGCouns: Journal of Professionals in Guidance and Counseling, 2023)
Thesis-writing students experience heightened academic stress due to the simultaneous demands of college assignments and thesis completion, leading to a significant sense of burden. A personality trait known as conscientiousness is characterized by adherence to obedient, organized,careful, determined, and disciplined behavior. This study examines the correlation between conscientiousness and academic stress among thesis-writing students in the Faculty of Economics and Business at a university in Indonesia. This study employs a quantitative correlational approach. The data collection techniques involve employing a simple random sampling method to gather information from a sample of 200 students from the Faculty of Economics and Business who are presently engaged in writing their theses. The study utilized the academic stress scale (Academic Stress Inventory) (Î± cronbach = 0.90) and the conscientiousness personality scale (Big Five Inventory) (Î± cronbach = 0.78) as measuring tools. SPSS tools are utilized in technical correlation analysis. The analysis reveals a significant negative correlation (r = -0.365, p < 0.01) between conscientiousness personality and academic stress among students at the Faculty of Economics and Business, currently engaged in thesis writing at the university. The relationship between conscientiousness and personality and academic stress reduction in students is positively correlated. This study recommends to provide psychoeducation programs for writing a thesis and seminars for students to develop the conscientiousness personality before preparing a thesis.